Survival in patients with class III idiopathic pulmonary arterial hypertension treated with first line oral bosentan compared with an historical cohort of patients started on intravenous epoprostenol. Issue 12 (29th July 2005) - Sitbon, O; McLaughlin, V V; Badesch, D B; Barst, R J; Black, C; Galiè, N; Humbert, M; Rainisio, M; Rubin, L J; Simonneau, G
Abstract : Background: The oral dual endothelin receptor antagonist bosentan improves exercise capacity and delays clinical worsening in patients with pulmonary arterial hypertension, but its use could delay starting intravenous epoprostenol, a life saving treatment. Methods: Survival in patients with functional class III idiopathic pulmonary arterial hypertension (PAH) treated with bosentan in clinical trials was compared with historical data from similar patients treated with epoprostenol in the clinic. Statistical methods were used to adjust for possible underlying differences between the two groups. Results: Baseline factors for the 139 patients treated with bosentan and the 346 treated with epoprostenol suggested that the epoprostenol cohort had more severe disease—that is, a lower cardiac index (2.01 v 2.39 l/min/m 2 ) and higher pressures and resistance. Kaplan-Meier survival estimates after 1 and 2 years were 97% and 91%, respectively, in the bosentan cohort and 91% and 84% in the epoprostenol cohort. Cox regression analyses adjusting for differences in baseline factors showed a greater probability of death in the epoprostenol cohort (hazard ratio 2.2 (95% confidence interval 1.2 to 4.0) in the model adjusted for haemodynamics). Alternative regression analyses and analyses to adjust for different data collection dates gave consistently similar results. When matched cohorts of 83 patients each were selected, survival estimates were similar. In the bosentan cohort 87% and 75% of patients followed for 1 and 2 years, respectively, remained on monotherapy. Conclusions: No evidence was found to suggest that initial treatment with oral bosentan, followed by or with the addition of other treatment if needed, adversely affected the long term outcome compared with initial intravenous epoprostenol in patients with class III idiopathic PAH.